Cadmium adsorption by an organic soil: a comparison of some humic - metal complexation models - Evans, Les J.; Sengdy, Boua; Lumsdon, David G.; Stanbury, Devon A. (Chemical speciation and bioavailability, 2003)
The retention of Cd by an organic soil was investigated as a function of pH and ionic strength. The adsorption of Cd at pH values from 2 to 11 at two ionic strengths (0.053 M and 0.017 M LiNO 3 ) were found to be a function of both pH and ionic strength. Four Cd-humic complexation models were evaluated in order to test the applicability of these models to fit data from batch adsorption experiments. The models varied greatly in their complexity and implicit assumptions. Three were discrete functional group models - a simple diprotic acid model, a two diprotic acid model and the Windermere Humic Aqueous Acid (WHAM) model, and a continuous functional group model - the non-ideal competitive adsorption (NICA) model. The concentration of proton binding sites in the soil was found to be 4.51 mol kg -1 . The NICA and WHAM models were more successful than either a simple diprotic acid model or a two diprotic acid model at modeling Cd complexation by the organic soil, although both underestimated adsorption at very high pH values.